Complications of Hypermature Cataract and Its Visual Outcome - Uzma Fasih, Erum Shahid, Arshad Sheikh (Pakistan Journal of Ophthalmology, 2011)
Purpose: To evaluate the additional complications of hyper mature cataract and their low visual outcome after extra capsular cataract extraction. Materials and Method: This study was conducted in the Department of Ophthalmology Abbasi Shaheed Hospital, Karachi from June 2006-2007. In this study evaluation of fifty patients with senile hyper mature cataract after preoperative assessment and investigations underwent extra capsular cataract extraction. Their surgical complications and postoperative complications were recorded. Their visual outcome was studied at each stage of follow up, conducted at 1st week, 3rd week, 6th week, 3rd month and 6th month. Best corrected visual acuity was obtained at 6 months. Result: Total of fifty patients 27 male and 23 female had extra capsular cataract extraction. 8 of the eyes had surgery complicated by posterior capsule rupture, vitreous loss, phacodonesis and drop nucleus. On first post operative day most common complication noted was striate keratitis (60%). Best corrected visual acuity at 6 months was 6/18 or more in 38(76%) patients. Conclusion: The operative and postoperative complication rate is higher in hyper mature cataracts. These complications can be reduced by early removal of cataract before it reaches the stage of hyper-maturity. Extra capsular surgery of hyper-mature cataract has good results after thorough preoperative assessment and if performed with expertise.